A De Novo Mutation Associated With Mandibular Hypoplasia, Deafness, Progeroid Features, and Lipodystrophy Syndrome in a Family With Werner Syndrome - Linda R. Wang MD; Aleksandar Radonjic BSc; Allison A. Dilliott BSc; Adam D. McIntyre BSc; Robert A. Hegele MD, FRCPC, FACP (SAGE Publishing, 2018)
Background. Mandibular hypoplasia, deafness, progeroid features, and lipodystrophy (MDPL) syndrome is a recently recognized genetic disorder comprised of mandibular hypoplasia, deafness, progeroid features, and lipodystrophy. It is caused by an autosomal dominant mutation in the POLD1 gene, with <20 genetically confirmed cases to date. Clinical overlap with other progeroid syndromes including Werner syndrome (WS) can present diagnostic challenges. Case. The proband is a 36-year-old male of Sicilian ancestry who was phenotypically normal at birth. Onset of lipodystrophic and progeroid features began at 18 months, with progressive loss of subcutaneous fat, prominent eyes, and pinched nose. Over the next 2 decades, he developed hearing loss, small fingers, joint contractures, hypogonadism, osteoporosis, and hypertriglyceridemia. Three of his 4 siblings had premature hair graying and loss, severe bilateral cataracts, skin changes, and varying degrees of age-related metabolic conditions, raising suspicion for a genetic progeroid syndrome. Genetic Analysis. A targeted sequencing panel identified a heterozygous WRN mutation in the proband's genomic DNA. Sanger sequencing further revealed his parents and an asymptomatic brother to be carriers of this mutation, and in his 3 brothers affected with classic WS the mutation was identified in the homozygous state. Whole exome sequencing ultimately revealed the proband harbored the causative de novo in-frame deletion in POLD1 (p.Ser605del), which is the most common mutation in MDPL patients. Conclusion. We report the unusual convergence of 2 rare progeroid disorders in the same family: the proband displayed sporadic MDPL syndrome, while 3 brothers had classical autosomal recessive WS. Whole exome sequencing was invaluable in clarifying the molecular diagnoses in this family.